Development of hematite ore pellet utilizing mill scale and iron ore slime combination as additive - Rajshekar Y.; Pal J.; Venugopalan T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Iron ore slime is generated from mines during processing and washing of iron ore, and it is not considered for pelletizing due to its excessive fineness and high gangue content, despite its good green bonding property. Mill scale is generated from steel rolling mills and reheating furnaces; it has almost nil gangue content, but is not individually considered for pelletizing due to its poor green bonding property. If both of these two wastes are blended in combined form with hematite ore, the high gangue of slime would be balanced by the gangue free mill scale. While mill scale provides exothermic heat of oxidation of FeO and Fe3O4 in it and enhance the diffusion bonding, slime provides good green bonding property to the pellet. Therefore, in this study a good quality pellet was developed by the combined mixing of these two wastes in hematite ore without much increase in gangue content. Up to 15% of mill scale and 15% of slime could be used successfully. The developed pellets provide improved cold compressive strength (366 kg/ pellet), reducibility index (82%), and reduction degradation index (8.5%). Induration temperature could be reduced by 75 °C, which indicates a considerable energy saving in induration furnace.